The Questions of Acquisition and Use of Operational Information in Urban Public Transport - Prileszky, I. (Acta Technica Jaurinensis, 2013)
In this article, we examine that beyond current standard methods which opportunities there are to obtain information about the traffic and in connection with this the use of this additional informations in planning and management.